2022
DOI: 10.1155/2022/7449941
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sulfur Clusters: A Key Factor of Regulated Cell Death in Cancer

Abstract: Iron-sulfur clusters are ancient cofactors that play crucial roles in myriad cellular functions. Recent studies have shown that iron-sulfur clusters are closely related to the mechanisms of multiple cell death modalities. In addition, numerous previous studies have demonstrated that iron-sulfur clusters play an important role in the development and treatment of cancer. This review first summarizes the close association of iron-sulfur clusters with cell death modalities such as ferroptosis, cuprotosis, PANoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 173 publications
0
3
0
Order By: Relevance
“…These Fe-S clusters are instrumental in directing various programmed cell death pathways, notably in ferroptosis and cuproptosis ( Figure 1 ). Their essentiality in apoptosis and PANoptosis also highlights their influence over the mitochondrial microenvironment, further underscoring their impact on cellular death processes ( Zhang et al, 2022 ).…”
Section: Panoptosis and Other Ion-related Cell Deathmentioning
confidence: 99%
“…These Fe-S clusters are instrumental in directing various programmed cell death pathways, notably in ferroptosis and cuproptosis ( Figure 1 ). Their essentiality in apoptosis and PANoptosis also highlights their influence over the mitochondrial microenvironment, further underscoring their impact on cellular death processes ( Zhang et al, 2022 ).…”
Section: Panoptosis and Other Ion-related Cell Deathmentioning
confidence: 99%
“…Tristetraprolin, expressed under iron-deficient conditions, was found to reduce the synthesis of various iron-binding proteins, especially iron-sulfur proteins, by degrading mRNA transcripts and maintaining the capacity of the cellular iron pool [ 78 ]. Furthermore, inhibition key proteins involved in the synthesis of iron-sulfur clusters, namely FXN and NSF1, can hinder the biosynthesis of said clusters, hasten the accumulation of free iron, and facilitate iron-induced cell death [ 79 ]. Upregulation of iron response element binding protein (IREB2) leads to increased synthesis of ferritin heavy and light chains of ferritin, as well as stable state of ferric ions in the steady state of ferritin [ 80 ].…”
Section: Iron Metabolism Regulationmentioning
confidence: 99%
“…ISC is an important inorganic cofactor that is widely engaged in a variety of biological functions including electron transfer which is the fundamental basis for cellular ATP production and protein synthesis. Meanwhile, recent studies have shown that ISC is tightly associated with DNA regulation ( 81 83 ).…”
Section: Recent Reports On Intrinsic Cellular Iron Metabolism and Fer...mentioning
confidence: 99%